2013
DOI: 10.4103/0974-8520.127724
|View full text |Cite
|
Sign up to set email alerts
|

Comparative pharmacognostical and phytochemical study on Bergenia ligulata Wall. and Ammania buccifera Linn

Abstract: “Pashanbheda” is a controversial plant. Pharmacopeia considers Bergenia ligulata as official source of Pashanbheda and official substitute is Avera lanta. Review of the literature reveals that 23 different plants are reported in name of “Pashanbheda”. Ammania buccifera is an adulterant, which is used in Kerala under the name of Pashanbheda, found in moist places of India. The present study was undertaken to compare the roots of both the plants and to have a brief view point on similarities and dissimilarities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…However, some endogenous antioxidants, such as glutathione peroxidase (GPX), superoxide dismutase (SOD), and catalase (CAT), provide a first-line defense against the free radicals [44,45]. Previous studies reported that bergenin and the plant sources Bergenia ciliate, Bergenia ligulata Wall, and Ficus racemose L. significantly restore the SOD, GPX, and CAT enzymes' activities [46][47][48]. It is also reported that bergenin exhibits a significant activity against free radicals [13].…”
Section: Discussionmentioning
confidence: 99%
“…However, some endogenous antioxidants, such as glutathione peroxidase (GPX), superoxide dismutase (SOD), and catalase (CAT), provide a first-line defense against the free radicals [44,45]. Previous studies reported that bergenin and the plant sources Bergenia ciliate, Bergenia ligulata Wall, and Ficus racemose L. significantly restore the SOD, GPX, and CAT enzymes' activities [46][47][48]. It is also reported that bergenin exhibits a significant activity against free radicals [13].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there was a near to normal restoration of the altered activity of carbohydrate metabolic enzymes as well as hepatic and kidney markers. Citronellol supplement preserved the histology of hepatic cells and pancreatic β-cells in streptozotocin-treated rats [124].…”
Section: Citronellolmentioning
confidence: 97%
“…Citronellol (3,7-dimethyl-6-octen-1-ol) is a linear monoterpene alcohol naturally found in about 70 essential oils, with abundance in Cymbopogon nardus (L.) and citrus oil [124,125]. Cymbopogon nardus was previously used in Chinese medicine to treat rheumatism, fever, and digestive problems [126].…”
Section: Citronellolmentioning
confidence: 99%
See 1 more Smart Citation
“…The plant has been used as a folk medicine since ancient times for dissolving kidney stones and is referred to as “ Paashanbheda” (Sanskrit: Paashan meaning “rockstone” and bheda meaning “piercing”) in the Indian traditional system of medicine— Ayurveda [ 7 ]. It has simple leaves of orbicular to obovate shape, stout root stock, and solid barrel-shaped cylindrical rhizome (1.5–3 cm in length and 1–2 cm in diameter) [ 8 ]. Himalayan communities consume the roots and rhizomes of the plant to treat wounds, septic, cough and cold, cardiac diseases, asthma, inflammation, gastrointestinal disorders, and different kinds of urinary problems [ 9 ].…”
Section: Introductionmentioning
confidence: 99%